2023
DOI: 10.3389/fmicb.2023.1097892
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the relationship between the gut microbiota enterotypes and colorectal adenoma

Abstract: IntroductionThe essence of enterotypes is to stratify the entire human gut microbiota, and dysregulation of gut microbiota is closely related to the development of colorectal adenoma. Enterotypes may therefore be a useful target for the prevention of colorectal adenoma. However, the relationship between gut microbiota and colorectal adenoma has not been fully elucidated. In this study, we aimed to analyze the differences in gut microbiome composition between adenoma and control populations.MethodsWe recruited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
3
2
0
Order By: Relevance
“…Consequently, the reported enterotypes vary among cohorts from different countries and races. The Escherichia-Shigella enterotype observed in our cohort is rarely found in the previous reports (Lu et al, 2021) but is consistent with the four other Chinese healthy cohorts (Liang et al, 2017;Lu et al, 2021;Lv et al, 2023;Pang et al, 2023). Overall, the present study confirms the role of age in Associations between age and gut microbiota diversity and composition have been observed both in our study and in others (de la Cuesta-Zuluaga et al, 2019;Zhang et al, 2021;Pang et al, 2023).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consequently, the reported enterotypes vary among cohorts from different countries and races. The Escherichia-Shigella enterotype observed in our cohort is rarely found in the previous reports (Lu et al, 2021) but is consistent with the four other Chinese healthy cohorts (Liang et al, 2017;Lu et al, 2021;Lv et al, 2023;Pang et al, 2023). Overall, the present study confirms the role of age in Associations between age and gut microbiota diversity and composition have been observed both in our study and in others (de la Cuesta-Zuluaga et al, 2019;Zhang et al, 2021;Pang et al, 2023).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, reports show that Prevotella and Bacteroides were two common enterotypes in Chinese populations (Lin et al, 2020). Escherichia-Shigella enterotype observed in our cohort is rare but consistent with the four other Chinese healthy cohorts (Liang et al, 2017;Lu et al, 2021;Lv et al, 2023;Pang et al, 2023). The alpha diversity indices (Shannon, observed species, Simpson, Pielou, ACE, and Chao1) were used to evaluate the diversity and richness of each enterotype.…”
Section: An Overview Of the Cohort And Analysis Of Enterotypessupporting
confidence: 91%
“…In addition, our findings showed that both mucosal enterotypes identified in CRC patients in our study cohort had a similar likelihood of being colonized by oral bacteria. Moreover, recent research has shown that the Prevotella-enriched enterotype may contribute to an increased occurrence of CRC [124], which aligns with the results obtained from our analysis, since the enterotype 2 was one of the most frequently detected in the intestinal samples of CRC patients.…”
Section: Discussionsupporting
confidence: 92%
“…This is the first enterotype-based meta-analysis of fecal metagenomic samples specific for CRC and ADN samples at species resolution. There have been few studies focusing on the changes in the gut microbiome of CRC or ADN patients stratified into different enterotypes, 37,68,69 however no distinct microbial species specific for enterotypes were proposed as diagnostic markers.…”
Section: Discussionmentioning
confidence: 99%